Overlooked complication of Cushing's syndrome: Reactivation of hepatitis B. (7th December 2022) - Barlas, Tugba; Yalcin, Mehmet Muhittin; Ozger, Hasan Selcuk; Altinova, Alev Eroglu; Akturk, Mujde; Toruner, Fusun Balos; Karakoc, Ayhan; Yetkin, Ilhan
Abstract: Objective: Individuals infected with hepatitis B virus (HBV) are at increased risk of reactivation when they receive immunosuppressive therapies. Although exogenous corticosteroid use as immunosuppressive therapy is elaborated in current guidelines on HBV reactivation, Cushing's syndrome (CS) with endogenous hypercortisolemia is not addressed. We aimed to investigate the prevalence of HBV infection and discuss the necessity of antiviral prophylaxis in patients with CS as in other immunosuppressed patients. Design and Patients: We included 72 patients with CS (Adrenocorticotropic hormone (ACTH) dependent or independent) who were screened for HBV between 2016 and 2021. Patients were categorized into three groups: overt, mild autonomous cortisol secretion (MACS), and remission according to the cortisol burden. Changes in patients' HBV serology and clinical findings over time were analyzed retrospectively. Results: Twenty‐six patients had overt hypercortisolism, 18 had mild autonomous cortisol secretion and 28 patients were in remission. Nineteen (26.3%) patients were anti‐HBc IgG positive, 4 of them were chronic HBV and 15 were isolated anti‐HBc IgG positive. HBsAg was positive in four (5.5%) of the patients, who were all compatible with inactive chronic HBV. While two patients developed HBV reactivation, HBV flare was observed in one patient. Conclusion: Since it is not always possible to achieve rapid remission in CS and these patients have long‐term hypercortisolemia, we suggest that consensus should be reached on HBV serological assessment, standardization of follow‐up, and planning of HBV prophylaxis in required instances in patients with CS especially in regions with a high prevalence of HBV infection.